A 3D ex vivo mandible slice system for longitudinal culturing of transplanted dental pulp progenitor cells. (11th May 2015) - Colombo, John S.; Howard‐Jones, Rachel A.; Young, Fraser I.; Waddington, Rachel J.; Errington, Rachel J.; Sloan, Alastair J.
Abstract Harnessing mesenchymal stem cells for tissue repair underpins regenerative medicine. However, how the 3D tissue matrix maintains such cells in a quiescent state whilst at the same time primed to respond to tissue damage remains relatively unknown. Developing more physiologically relevant 3D models would allow us to better understand the matrix drivers and influence on cell‐lineage differentiation in situ. In this study, we have developed an ex vivo organotypic rat mandible slice model; a technically defined platform for the culture and characterization of dental pulp progenitor cells expressing GFP driven by the β‐actin promoter (cGFP DPPCs). Using confocal microscopy we have characterized how the native environment influences the progenitor cells transplanted into the dental pulp. Injected cGFP‐DPPCs were highly viable and furthermore differentially proliferated in unique regions of the mandible slice; in the dentine region, cGFP‐DPPCs showed a columnar morphology indicative of expansion and lineage differentiation. Hence, we demonstrated the systematic capacity for establishing a dental pulp cell‐micro‐community, phenotypically modified in the tooth (the "biology"); and at the same time addressed technical challenges enabling the mandible slice to be accessible on platforms for high‐content imaging (the biology in a "multiplex" format). © 2015 The Authors. Published by Wiley Periodicals, Inc.